TRIM21 functions as an oncogene in glioblastoma by transactivating FOSL1 and promoting the ubiquitination of p27 - Vanajothi Ramar; Rajveer Singh Sidhu; Osei Pako; Cheyenne R. Cisse; Alyssa A. Guo; Jason Li; Kelcey Stapleton; Shanchun Guo; Guangdi Wang; Mingli Liu (Cell Communication and Signaling)
Abstract Our previous studies demonstrated that FOSL1 promotes glioblastoma (GBM) progression and stemness through pathways such as STAT3 and NF-κB signaling. Recently, we identified that FOSL1 physically interacts with the nuclear E3 ligase TRIM21. This study investigates the role of TRIM21 in GBM, including its interaction with FOSL1, its regulation of FOSL1 transactivation, and its ubiquitination-mediated degradation of tumor suppressor p27. Immunoprecipitation assays were used to evaluate the interactions between TRIM21, FOSL1, and p27. TRIM21 expression was manipulated through overexpression and siRNA-mediated knockdown to assess its effects on p27 levels and ubiquitination. TCGA and CGGA datasets were analyzed to explore correlations between TRIM21 expression, glioma subtypes, and patient survival. Glioma cell proliferation (MTT and colony formation) and invasion (transwell assays) were evaluated following TRIM21 manipulation. Immunohistochemistry on glioma patient tissue microarray (TMA) assessed TRIM21 expression and its association with FOSL1, IDH status, and glioma grade. The role of nuclear TRIM21 in FOSL1 promoter transactivation was analyzed via AP-1 binding sites. TCGA and CGGA revealed that TRIM21 is highly expressed in GBM, particularly in the mesenchymal subtypes, and correlates with poor survival outcomes. Functional assays demonstrated that TRIM21 enhances glioma cell proliferation and invasion. Immunohistochemistry confirmed elevated TRIM21 levels in gliomas, positively correlating with FOSL1 expression and glioma grade, and inversely correlating with IDH1 wild-type status. Mechanistically, TRIM21 physically interacts with FOSL1 and p27, driving tumorigenesis by transactivating FOSL1 via AP-1 binding sites and promoting p27 ubiquitination and degradation. These functions are mediated through TRIM21’s RING domain for p27 degradation and its PRYSPRY domain for FOSL1 regulation. TRIM21 functions as an oncogene in GBM by degrading the tumor suppressor p27 and promoting FOSL1 transactivation. These findings highlight TRIM21 as a promising therapeutic target in GBM.